Keanekaragaman Makrozoobentos Sebagai Indikator Kualitas Air di Hutan Mangrove Pantai Kuri Caddi di Kabupaten Maros - Yasir Yasyfa Amin; Jamaluddin Jamaluddin; Ernawati S. Kaseng (Peneliti.net, 2023)
Kuri Caddi Beach is located in Kuri Caddi Hamlet, Nisombalia Village, Marusu District, Maros Regency, South Sulawesi Province. Kuri Caddi Beach has potential natural resources consisting of 23 types of mangroves. Macrozoobenthos are invertebrate animals that live on the bottom of the water. The purpose of this study was to determine the diversity of macrozoobenthos in the mangrove forest and the condition of the waters in the mangrove forest of the Kuri Caddi coast, Maros Regency. This research is a type of quantitative descriptive research using a survey method which was carried out from February to March 2021. This research was carried out by taking macrozoobenthos samples and air samples from three observations found in the mangrove forest of the Kuri Caddi coast. The results showed that the diversity index value ranged from 1.4001 to 1.9554 which was classified as moderate, the uniformity index ranged from 0.8854 to 0.9597 which was classified as high, the dominance index value ranged from 0.1397 to 0.2300 which was classified as low and There are 3 classes of macrozoobenthos in the coastal mangrove forest of Kuri Caddi, namely Gastropods, Bivalves, Crustaceans with a total of 9 species, namely Chicoreus Capucinus, Terebralia Sulcata, Nerita Undata, Nerita Signata, Pirenella Incisia, Ceratodesma Edule,Periglypta Puerpera, Uca Sp. and Ilyoplaks Sp.